Respostas morfofisiológicas e herança materna para tolerância à seca em progênies de café conilon - Sobreira, Franciele Barros de Souza (2017)
Coffee is currently one of the major commodities in Brazil. Among many works carried out aiming at the improvement of this culture, the search for materials more adapted to the climatic variations, especially the drought has been highlighted. This fact is mainly due to the climatic changes that are occurring in many Brazilian regions. The morphological and physiological analyzes of the plants have aided in the selection of drought tolerant genotypes for the evaluation of superiority in breeding programs. The present study aimed at evaluating the morphophysiological characteristics of conilon progenies submitted to drought, evaluating the plant morphology, photosynthesis and chemical quantification of foliar tissues, to verify the variability of the progenies, to evaluate the possibility of extrachromosomal maternal inheritance for drought tolerance and to identify more drought tolerant genotypes. The experiment was conducted at the Experimental Farm of the Marilândia-ES Incaper and two populations of Coffea canephora, derived from the cross between the susceptible clone 109 and the drought tolerant clone 120 (120x109 and 109x120) were used. For the evaluation of the experiment and conclusions of the results was used to descriptive statistics and principal component analyzes (PCA). It was observed through the measures of position and dispersion that there were many changes between the variables throughout the analysis period (July/2015, December/2015 and April/2016), wide variability among individuals within each evaluation period and that in April 2016 it was the most critical period of drought, among the evaluated periods, occurring, most of the time, decreases in the means of the analyzed parameters and greater variations in the progenies. In July and December 2015 the population 109x120 presented the highest averages, however in April 2016 the population 120x109, showed higher averages. These changes were allied to extrachromosomal maternal inheritance, mainly chloroplast, due to differences in the means of reciprocal crosses, for most variables. There was a greater manifestation of the characteristics of clone 109, as pollen recipient mother, in July and December of 2015, in the progenies 109x120, period of greater hydration of the plants. In April 2016, critical period of drought, there was a greater manifestation of clone 120, in the population 120x109, so it presented better means. Due to the variabilities observed among the individuals, the PCA were used to identify the parameters that best represented the variation among the individuals. Ten parameters were evaluated in July, nine in December and April in all individuals, demonstrating that approximately 80% of the observed variation can be explained by five and six principal xii components (PC) in the population 120x109, and four and five components in the 109x120. Each PC represented a proportion of the variation and was correlated in different degrees to the measured parameters. Attention was drawn to the information from PC1 and PC2, in April 2016, showing a better growth condition in the 120x109 population, due to the high positive correlation with RAF (leaf area ratio), AFU (unit leaf area), AFE (leaf area specific), FT (total phenol), proline and ETR (electron transport rate), which are important correlations between the variables, for the development of plants under conditions of water stress. Due to the different correlations of the PCA with the parameters, a hierarchical UPGMA grouping, based on average euclidean distance, was performed to discriminate the differentiations between the individuals. For the population 120x109, eight groups were identified in July/2015, ten in December/2015 and seven in April/2016. For the population 109x120, four groups in July/2015, three in December/2015 and three in April/2016. Based on average of the groups for each parameter, it was found that in April 2016, a critical period of drought, some individuals managed to maintain better morphophysiological characteristics, such as those presented in groups 3, 5 and 7, represented by individuals 1, 2, 12, 13, 17, 26, 28, 50 and 58 of the population 120x109, demonstrating phenological highlight to tolerate more drought, being the AFE, RAF, A, ETR, gs and A/gs variables more relevant for genotype discrimination. Genotypes 1, 26, 56 and 58 showed greater dissimilarity, but individual 56 was more characterized as susceptible to drought. It has also been shown that there are other individuals that have similar characteristics to those selected for tolerance and that deserve to be better explored, such as individuals 8, 9, 14, 22, 25, 29 for tolerance and genotypes 20, 21, 23, 31, 32, 33, 34, 35 for drought susceptibility. In summary, most of the mechanisms of resistance to drought in conilon coffee are governed by extrachro